A case of microwave coagulation therapy applied to hemostasis in the endoscopic vesical lithotripsy - Fukuda, Takashi; Kigure, Teruaki; Tsuchida, Seigi; Togashi, Hisafumi; Satoh, Yoshinobu; Suzuki, Takehiro; Yuri, Yasuhiro; Harada, Tadashi (Journal of Microwave Surgery, 1995)
The case is 76-year-old male whose chief complaint was terminal miction pain. A urinalysis showed microscopic hematuria and pyuria, and KUB revealed a 5.0 × 3.3 cm sized vesical calculus. Transurethral vesical lithotripsy using a pyeloscope was performed. Microwave coagulation therapy was applied to hemostasis which was interrupted the lithotripsy. The coagulation was performed with a microwave energy of 100 watts for 30 seconds. There was not any inconvinience, when the microwave applicator was inserted through the pyeloscope. The operation was able to be performed safely to the end. It supposed that the microwave coagulation therapy was a useful combined procedure for the endoscopic treatment of urinary tracts calculi.